2013
DOI: 10.1016/j.eswa.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Chain Ladder: Reformulating and generalizing a classical insurance problem

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 38 publications
(17 reference statements)
0
38
1
Order By: Relevance
“…The CLM forecast uses f CL (l), the CLM estimate for the density of claim duration l, which is given in equation (A1) in the Appendix A. The density representation of the CLM is presented in greater detail in Martínez-Miranda et al (2013). The second forecast, O…”
Section: Forecast Amentioning
confidence: 99%
See 1 more Smart Citation
“…The CLM forecast uses f CL (l), the CLM estimate for the density of claim duration l, which is given in equation (A1) in the Appendix A. The density representation of the CLM is presented in greater detail in Martínez-Miranda et al (2013). The second forecast, O…”
Section: Forecast Amentioning
confidence: 99%
“…Observed data triangle: O tl regression problem, seeMartínez-Miranda et al (2013). The goal is to estimate t and l .…”
mentioning
confidence: 99%
“…Neither of these attempts performed as well as the do-validated bandwidth. It would be interesting to see whether indirect cross-validation and do-validation would also be useful to improve other variants of the kernel density estimation problem, such as the problem considered by Gavriliadis and Athanassoulis (2012), Park (2013), Eidous (2012) or Martínez-Miranda et al (2013).…”
Section: Simulation Experiments About Indirect Do-validationmentioning
confidence: 99%
“…In a nonparametric universe, the estimators resulting from the multiplicative Poisson models are structured histograms. Martínez-Miranda et al (2013) showed the link between actuarial parametric chain ladder-type models [Kuang, Nielsen and Nielsen (2009)] and structured smoothing as considered in this paper.…”
Section: Introductionmentioning
confidence: 99%